2020
DOI: 10.3390/jcm9040968
|View full text |Cite
|
Sign up to set email alerts
|

Transient Existence of Circulating Mesenchymal Stem Cells in the Deep Veins in Humans Following Long Bone Intramedullary Reaming

Abstract: The biology of mesenchymal stem cells (MSCs) in humans is incompletely understood and a possible role of systemically circulating cells in health and autoimmune disease remains controversial. Physiological movement of bone marrow MSCs to sites of injury would support the rationale for intravenous administration for relocation to damaged organs. We hypothesized that biophysical skeletal trauma rather than molecular cues may explain reported MSC circulation phenomena. Deep-femoral vein (FV) and matched periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…After being mobilized, these local MSCs are recruited to the site of injury where they participate in the healing process (Xu and Li, 2014). Another hypothesis supports that the very rare presence of MSCs is likely linked to biophysical microdamage rather than the fact that specific molecular cues to a circulatory pool of MSCs are capable of repairing remote organs or tissues (Churchman et al, 2020). Several groups have revealed that MSCs, after infusion, activate complement by unknown mechanisms, leading to their damage and disappearance.…”
Section: Complementmentioning
confidence: 98%
“…After being mobilized, these local MSCs are recruited to the site of injury where they participate in the healing process (Xu and Li, 2014). Another hypothesis supports that the very rare presence of MSCs is likely linked to biophysical microdamage rather than the fact that specific molecular cues to a circulatory pool of MSCs are capable of repairing remote organs or tissues (Churchman et al, 2020). Several groups have revealed that MSCs, after infusion, activate complement by unknown mechanisms, leading to their damage and disappearance.…”
Section: Complementmentioning
confidence: 98%
“…КЛЕТОЧНАЯ БИОЛОГИЯ, ЦИТОЛОГИЯ, ГИСТОЛОГИЯ Как известно, при повреждении тканей МСК способны выходить в системный кровоток для последующей миграции в пораженную область [6,66]. Их мобилизация из депо в периферическую кровь может быть стимулирована путем внутривенного введения гранулоцитарного колониестимулирующего фактора (granulocyte colony-stimulating factor, G-CSF) [67,68], гранулоцитарно-макрофагального колониестимулирующего фактора (granulocyte macrophage colony-stimulating factor, GM-CSF) [69], TGF-β [70], субстанции P [71], VEGF [71].…”
Section: активация эндогенных мскunclassified
“…An interesting aspect of the use of culture-expanded MSCs as effector cells for immunomodulation in RA is that these cells are given intravenously. However, there is little evidence for the physiological circulation of MSCs in humans, including patients with RA ( 49 ), which will be discussed further in this review.…”
Section: Msc Function In Healthy Jointsmentioning
confidence: 99%